Compression Independent Reversible Encryption for Privacy in Video Surveillance. (8th February 2010) - Carrillo, Paula; Kalva, Hari; Magliveras, Spyros
Abstract : One of the main concerns of the wide use of video surveillance is the loss of individual privacy. Individuals who are not suspects need not be identified on camera recordings. Mechanisms that protect the identity while ensuring legitimate security needs are necessary. Selectively encrypting regions that reveal identity (e.g., faces or vehicle tags) are necessary to preserve individuals' right to privacy while recognizing the legitimate needs for video surveillance. The video used in surveillance applications usually needs to be transcoded or recoded for distribution and archival. Transcoding a traditionally encrypted video is not possible without decrypting the video first. This paper presents a compression algorithm independent solution that provides privacy in video surveillance applications. The proposed approach uses permutation-based encryption in the pixel domain to hide identity revealing features. The permutation-based encryption tolerates lossy compression and transcoding and allows decryption of the transcoded video at a later time. The use of permutation-based encryption makes the proposed solution independent of the compression algorithms used and robust to transcoding. The cost of providing this privacy is an increase in bitrate that depends on the percentage of blocks encrypted.